Usage Patterns And Safety Awareness Of Nsaids (Non-Steroidal Anti-Inflammatory Drugs) Among The Rural Population In Kerala A Cross-Sectional Survey - Shifan K, Mohamed; Ravi, Krishna; Simon, Alwin (Journal of Neonatal Surgery, 2025)
Background: The widespread use of NSAIDs as over the counter medicines (OTCs) raises concern on patient safety. Current study investigated and evaluated the usage patterns, safety awareness, and potential risks of NSAID use among the rural population of Kerala. Methodology: The cross-sectional observational study was conducted among people residing in rural areas of Malapuram, Kerala, India, who were taking NSAIDs with or without prescription for their pain management. The sample size was determined using a statistical formula that accounts for the expected prevalence of NSAID use based on preliminary studies or surveys.8 Total of 390 participants were participated in the survey. Awareness and Knowledge of NSAID use, Self-Medication Practices. Results: The study surveyed 407 participants, with 390 included in the final analysis. The participants were categorized as occasional and regular users. The results showed that NSAID use increased with age, particularly among females aged 21-60 years. The most common reasons for NSAID use were back and muscle pain, followed by headaches and menstrual cramps. A significant portion of participants who used NSAIDs occasionally (66.92%) were self-medicated, and 29.23% used them regularly without prescription. Gastrointestinal issues like dyspepsia and epigastric pain were common side effects, particularly among regular users. Conclusion: This study analyzed NSAID use patterns in the rural population of Kerala, focusing on demographics, usage patterns, and side effects. Most participants (66.92%) were self-medicated with NSAIDs, while only 2.56% used prescription NSAIDs. Regular use was less common but more prevalent among females and gastrointestinal side effects, especially epigastric pain and dyspepsia, were more frequent in regular users, underscoring the need for caution with long-term use. Since there was a gap in knowledge and awareness regarding NSAID use risks, indicating a need for better safety education.